Hero wanted - Krahn, Betina M. (Krahn, Betina M. Reluctant heroes, 2021)
"When dashing, determined bachelor Rafe Townsend, and beautiful, impetuous Lauren Alcott are trapped into an engagement by their powerful business magnate fathers, their attraction suggests there may be pleasurable compensations to matrimony after all. Until an outing together puts a damper on their future... Lauren is appalled when Rafe refuses to help two women whose boat has overturned on a river. Stripping her outer clothing, she dives in to rescue them herself--delighting a nearby reporter. Soon newspapers and scandal sheets have labeled Rafe as less than heroic, for all of London to see, while Lauren is viewed by many as brazen. Besieged by scandalous rumors, and with both their reputations in the balance, what ensues is a prickly scheme that will either forge a partnership of deception--or blaze a path to true love..."--Publisher's description.